Cozy Homes? Rooms and apartments of the intelligentsia in Polish drama films, 1956–1970 - Gierszewska, Barbara Lena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article presents the problems of private life of intellectuals in Poland “after Yalta” through the prism of the cinema. The biggest problem of people in the 1950s and 1960s was the lack of a satisfying home. The homes of young intellectuals shown in Polish films are the spectrum of dreams, most often impossible to achieve in real life. Apartments located in multi-family housing estates that immortalized in the Polish feature films between the years 1956–1970 are confirmation of the highest quality of Polish industrial design. Real people’s apartments were cramped, ugly, and primitive.